Lithium ion battery negative electrode slurry, preparation method thereof, pole piece and lithium ion battery
By using a slurry preparation method of high-content negative electrode main material in the negative electrode sheet of lithium-ion battery, the problems of low content of negative electrode main material, high resistivity and low adhesion force are solved, and better low-temperature charging performance and cost-effectiveness are achieved.
Patent Information
- Application Number
- CN202411675522.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-07
AI Technical Summary
The negative electrode main material content in the lithium-ion battery negative electrode sheet is low, the electrode sheet resistivity is large, and the adhesion force is small, resulting in poor low-temperature charging performance and high battery cell cost.
Using a preparation method for lithium-ion battery negative electrode slurry, the negative electrode active material, conductive agent and polyacrylic acid (PAA) binder are mixed in a specific proportion, and additives and solvents are added to form an electrode sheet with a high content of the negative electrode main material.
The content of the negative electrode main material is improved, the resistivity of the electrode sheet is reduced, the peeling force and structural stability of the electrode sheet are enhanced, the low-temperature charging performance of the battery is improved, and the cost is reduced.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a lithium ion battery negative electrode slurry and a preparation method thereof, a pole piece and a lithium ion battery. Background Art
[0002] The traditional lithium-ion negative electrode sheet preparation method includes negative electrode active materials, conductive agents, dispersants, binders, solvents, and current collectors. There are many types of materials, low content of negative electrode main materials, and low production efficiency. The binder is mainly made of styrene-butadiene rubber latex, which has large impedance, large electrode sheet resistivity, poor low-temperature charging performance of the battery, good electrode sheet toughness, and poor dynamic performance. It is necessary to increase the conductive agent content and reduce the impedance, resulting in low content of negative electrode main materials, low energy density of the battery cell, and high cost of the battery cell. Summary of the invention
[0003] The main purpose of the present invention is to provide a lithium ion battery negative electrode plate and a preparation method thereof, and a lithium ion battery, so as to overcome the problems of low negative electrode main material content, high electrode resistivity and low bonding force of the lithium ion negative electrode plate.
[0004] To achieve the above object, the present invention provides a method for preparing a negative electrode slurry for a lithium ion battery, comprising: S1, providing a negative electrode active material, a conductive agent and a PAA binder according to 92-97%, 0.5-4% and 2.5-4% of the total mass ratio, and providing an auxiliary agent according to a ratio of 0.8%-3.0% of the mass of the negative electrode active material, wherein the auxiliary agent is one or a combination of ethanol, isopropanol, N-methylpyrrolidone (NMP), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethylene glycol; S2, mixing the negative electrode active material, the conductive agent and 50%-70% of the PAA binder, adding a solvent, kneading and stirring to obtain a mixture; S3, adding the remaining PAA binder, the remaining solvent and the auxiliary agent to the mixture obtained in step S2, and stirring to obtain the lithium ion battery negative electrode slurry; The solvent used in step S2 accounts for 35-45% of the total solvent, and the total mass of the solvent in step S2 and step S3 accounts for 25-65% of the total mass of the negative electrode slurry.
[0005] Furthermore, the solvent is deionized water. The auxiliary agent is preferably ethylene carbonate (EC), isopropanol, and N-methylpyrrolidone (NMP).
[0006] Furthermore, the negative electrode active material comprises one or a combination of graphite, soft carbon, hard carbon, silicon oxygen, silicon carbon, silicon alloy, tin alloy, and other non-carbon negative electrode materials; the conductive agent comprises one or a combination of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, VGCF, and conductive paste.
[0007] Furthermore, the negative electrode active material is graphite, and the conductive agent is carbon black.
[0008] Furthermore, the step S2 specifically includes: slowly stirring and mixing the negative electrode active material, the conductive agent and 50%-70% of the PAA binder at a revolution speed of 10-15 r / min and a rotation speed of 200-400 r / min, and then adding a solvent to knead and stir to obtain the mixture; the step S specifically includes: adding the remaining PAA binder, solvent and auxiliary agent to the mixture obtained in step S2, and rapidly stirring at a revolution speed of 15-18 r / min and a rotation speed of 1200-1800 r / min to obtain the lithium-ion battery negative electrode slurry.
[0009] The present invention also provides a negative electrode slurry for a lithium ion battery, which is prepared by the method for preparing the negative electrode slurry for a lithium ion battery as described in any one of the above items.
[0010] The present invention also provides a lithium ion battery negative electrode plate, comprising a current collector and a negative electrode active material layer formed by drying a negative electrode slurry coated on the current collector, wherein the negative electrode slurry is the above-mentioned lithium ion battery negative electrode slurry.
[0011] Furthermore, the current collector is one of copper foil, microporous copper foil, coated copper foil, aluminum foil, microporous aluminum foil, and coated aluminum foil, and has a thickness of 3µm-20µm.
[0012] Furthermore, the current collector is 6µm copper foil.
[0013] The present invention also provides a lithium ion battery, comprising the lithium ion battery negative electrode sheet as described in any one of the above items.
[0014] The present invention provides a negative electrode slurry for a lithium ion battery and a preparation method thereof, a pole piece and a lithium ion battery, wherein the negative electrode pole piece comprises a negative electrode active material, a conductive agent, PAA, an auxiliary agent, a solvent and a current collector.
[0015] Polyacrylic acid PAA has excellent bonding properties and good dispersion effects. PAA belongs to line bonding, with a higher degree of anchoring of particles, stronger cohesion of the pole piece, and is conducive to structural stability. SBR / CMC focuses on point-to-point bonding between particles, and the pole piece rebounds after compaction and expands more after injection. Water-based PAA contains a high proportion of strong polar groups such as sodium carboxylate, which has a better bonding effect on the current collector. The working principle of PAA (polyacrylic acid) as a dispersant is mainly to permanently break up various powdered and solid substances through the function of surfactant. The main chain of PAA molecules contains a large number of carboxyl groups, which can form a strong electrochemical reaction with the surface of solid substances and produce a large number of bonding effects, thereby dispersing the particles into the aqueous solution, reducing the interaction force between particles, and evenly dispersing the aggregated powder texture into the water. Water-based binders containing -COOH and -CN (such as PAA) have lone electron pairs in the O and N elements contained in the group. Under the action of the electric field, they continuously complex and decomplex with lithium ions, thereby promoting the diffusion of lithium ions. A higher Tg is beneficial to maintaining the structure of the electrode, maintaining a certain porosity, and is beneficial to the diffusion channel of lithium ions, and has good kinetic performance. The water-based binder containing -COOH and -CN has a small impedance, a small resistivity of the pole piece, and good low-temperature charging performance of the battery, but the high Tg and strong intermolecular hydrogen bonding make the slurry easy to settle and the pole piece brittle.
[0016] PAA powder is added in two steps. The first part of PAA powder is mainly used to replace the traditional CMC, used to coat the negative electrode main material, and play a dispersing role. The second part of PAA powder replaces the traditional negative electrode binder, allowing the negative electrode slurry to adhere well to the foil. PAA powder replaces traditional dispersants and binders. Simplify the types of negative electrode slurry materials, increase the content of negative electrode main materials, reduce the resistivity of the pole piece, and enhance the pole piece peeling force.
[0017] Additives can destroy the hydrogen bonds between molecules, improve the brittleness of the electrode, increase the toughness of the electrode, and reduce the possibility of cracking of the electrode during coating. DETAILED DESCRIPTION
[0018] The following is a clear and complete description of the technical problems solved by the embodiments of the present invention, the technical solutions adopted, and the technical effects achieved in combination with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other equivalent or obviously modified embodiments obtained by ordinary technicians in this field without creative work fall within the protection scope of the present invention. The embodiments of the present invention can be concretized in a variety of different ways as defined and covered in the claims.
[0019] It should be noted that in the following description, many specific details are given for ease of understanding, but it is obvious that the present invention can be implemented without these specific details.
[0020] It should be noted that, in the absence of clear limitation or conflict, the various embodiments of the present invention and the technical features therein can be combined with each other to form a technical solution.
[0021] Embodiment 1: The preparation method of the negative electrode sheet of a lithium-ion battery is as follows: Negative electrode active material: graphite / total powder mass = 94.7% Negative electrode conductive agent: conductive carbon black SuperP / total powder mass = 1.5% Negative electrode dispersant: CMC-Na / total powder mass = 1.3% Negative electrode binder: styrene-butadiene rubber powder / total powder mass = 2.5%, styrene-butadiene rubber latex solid content is 40%, solvent is water Anode solvent: deionized water Negative electrode current collector: 6µm electrolytic copper foil.
[0022] The method for preparing the negative electrode slurry of a lithium ion battery comprises the following steps: ① Take 100kg of graphite, 1.37kg of CMC-Na and 1.58kg of conductive carbon black and add them into a stirring tank. Stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 25min. ② Add 44.12kg of deionized water and stir at a revolution rate of 15r / min and a rotation rate of 300r / min for 70min ③ Add 57.51 kg of deionized water and stir at a revolution rate of 18 r / min and a rotation rate of 1200 r / min for 70 min. ④ Add 6.6kg of styrene-butadiene rubber latex, stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 30min, and filter to obtain a slurry ⑤ Apply the slurry obtained above onto 6µm electrolytic copper foil, dry and die-cut to obtain the negative electrode sheet.
[0023] Embodiment 2: The preparation method of the negative electrode sheet of a lithium-ion battery is as follows: Negative electrode active material: graphite / total powder mass = 93.7% Negative electrode conductive agent: conductive carbon black SuperP / total powder mass = 2.5% Negative electrode dispersant: CMC-Na / total powder mass = 1.3% Negative electrode binder: styrene-butadiene rubber powder / total powder mass = 2.5%, styrene-butadiene rubber latex solid content is 40%, solvent is water Anode solvent: deionized water Negative electrode current collector: 6µm electrolytic copper foil The method for preparing the negative electrode slurry of a lithium ion battery comprises the following steps: ① Take 100kg of graphite, 1.38kg of CMC-Na and 2.66kg of conductive carbon black and add them into a stirring tank. Stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 25min. ② Add 44.59 kg of deionized water and stir at a revolution rate of 15 r / min and a rotation rate of 300 r / min for 70 min. ③ Add 58.12 kg of deionized water and stir at a revolution rate of 18 r / min and a rotation rate of 1200 r / min for 70 min. ④ Add 6.67kg of styrene-butadiene rubber latex, stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 30min, and filter to obtain a slurry. ⑤ Apply the slurry obtained above onto 6µm electrolytic copper foil, dry and die-cut to obtain the negative electrode sheet.
[0024] Embodiment 3: The preparation method of the negative electrode sheet of a lithium-ion battery is as follows: Negative electrode active material: graphite / total powder mass = 92.2% Negative electrode conductive agent: conductive carbon black SuperP / total powder mass = 4% Negative electrode dispersant: CMC-Na / total powder mass = 1.3% Negative electrode binder: styrene-butadiene rubber powder / total powder mass = 2.5%, styrene-butadiene rubber latex solid content is 40%, solvent is water Anode solvent: deionized water Negative electrode current collector: 6µm electrolytic copper foil.
[0025] The method for preparing the negative electrode slurry of a lithium ion battery comprises the following steps: ① Take 100kg of graphite, 1.40kg of CMC-Na and 4.33kg of conductive carbon black and add them into a stirring tank. Stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 25min. ② Add 45.32kg of deionized water and stir at a revolution rate of 15r / min and a rotation rate of 300r / min for 70min ③ Add 59kg of deionized water and stir at a revolution rate of 18r / min and a rotation rate of 1200r / min for 70min ④ Add 6.77kg of styrene-butadiene rubber latex, stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 30min, and filter to obtain a slurry. ⑤ Apply the slurry obtained above onto 6µm electrolytic copper foil, dry and die-cut to obtain the negative electrode sheet.
[0026] Comparison Group 1: The preparation method of the negative electrode sheet of a lithium-ion battery is as follows: Negative electrode active material: graphite / total powder mass = 96% Negative electrode conductive agent: conductive carbon black SuperP / total powder mass = 1.5% Negative electrode PAA powder: PAA powder / total powder mass = 2.5%, the amount of PAA powder added in the first step is 0.5 of the total PAA powder Negative electrode additive: EC, additive is 2% of the mass of negative electrode active material Anode solvent: deionized water Negative electrode current collector: 6µm electrolytic copper foil.
[0027] The method for preparing the negative electrode slurry of a lithium ion battery comprises the following steps: ① Take 100kg of graphite, 1.30kg of PAA and 1.56kg of conductive carbon black and add them into a stirring tank. Stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 25min. ② Add 44.64 kg of deionized water and stir at a revolution rate of 15 r / min and a rotation rate of 300 r / min for 70 min. ③ Add 1.30kg PAA, 59.52kg deionized water, and 2kg EC, and stir at a revolution rate of 18r / min and a rotation rate of 1200r / min for 70min. ④ Stir at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and filter to obtain a slurry ⑤ Apply the slurry obtained above onto 6µm electrolytic copper foil, dry and die-cut to obtain the negative electrode sheet.
[0028] Comparison Group 2: The preparation method of the negative electrode sheet of a lithium-ion battery is as follows: Negative electrode active material: graphite / total powder mass = 95% Negative electrode conductive agent: conductive carbon black SuperP / total powder mass = 2.5% Negative electrode PAA powder: PAA powder / total powder mass = 2.5%, the amount of PAA powder added in the first step is 0.5 of the total PAA powder Negative electrode additive: EC, additive is 2% of the mass of negative electrode active material Anode solvent: deionized water Negative electrode current collector: 6µm electrolytic copper foil.
[0029] The method for preparing the negative electrode slurry of a lithium ion battery comprises the following steps: ① Take 100kg of graphite, 1.31kg of PAA and 2.63kg of conductive carbon black and add them into a stirring tank, and stir them at a revolution rate of 10r / min and a rotation rate of 300r / min for 25min.
[0030] ② Add 45.11 kg of deionized water and stir at a revolution rate of 15 r / min and a rotation rate of 300 r / min for 70 min. ③ Add 1.31kg PAA, 60.15kg deionized water, and 2kg EC, and stir at a revolution rate of 18r / min and a rotation rate of 1200r / min for 70min. ④ Stir at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and filter to obtain a slurry ⑤ Apply the slurry obtained above onto 6µm electrolytic copper foil, dry and die-cut to obtain the negative electrode sheet.
[0031] Comparison group 3: The preparation method of the negative electrode sheet of a lithium-ion battery is as follows: Negative electrode active material: graphite / total powder mass = 93.5% Negative electrode conductive agent: conductive carbon black SuperP / total powder mass = 4% Negative electrode PAA powder: PAA powder / total powder mass = 2.5%, the amount of PAA powder added in the first step is 0.5 of the total PAA powder Negative electrode additive: EC, additive is 2% of the mass of negative electrode active material Anode solvent: deionized water Negative electrode current collector: 6µm electrolytic copper foil.
[0032] The method for preparing the negative electrode slurry of a lithium ion battery comprises the following steps: ① Take 100kg of graphite, 1.33kg of PAA and 4.27kg of conductive carbon black and add them into a stirring tank. Stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 25min. ② Add 45.82kg of deionized water and stir at a revolution rate of 15r / min and a rotation rate of 300r / min for 70min ③ Add 1.33kg PAA, 61.11kg deionized water, and 2kg EC, and stir at a revolution rate of 18r / min and a rotation rate of 1200r / min for 70min. ④ Stir at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and filter to obtain a slurry ⑤ Apply the slurry obtained above onto 6µm electrolytic copper foil, dry and die-cut to obtain the negative electrode sheet.
[0033] Comparison group 4: The preparation method of the negative electrode sheet of a lithium-ion battery is as follows: Negative electrode active material: graphite / total powder mass = 96% Negative electrode conductive agent: conductive carbon black SuperP / total powder mass = 1.5% Negative electrode PAA powder: PAA powder / total powder mass = 2.5%, the amount of PAA powder added in the first step is 0.8 of the total PAA powder Negative electrode additive: EC, additive is 2% of the mass of negative electrode active material Anode solvent: deionized water Negative electrode current collector: 6µm electrolytic copper foil.
[0034] The method for preparing the negative electrode slurry of a lithium ion battery comprises the following steps: ① Take 100kg graphite, 2.08kg PAA and 1.56kg conductive carbon black and add them into the stirring tank. Stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 25min. ② Add 44.64 kg of deionized water and stir at a revolution rate of 15 r / min and a rotation rate of 300 r / min for 70 min. ③ Add 0.52kg PAA, 59.52kg deionized water, and 2kg EC, and stir at a revolution rate of 18r / min and a rotation rate of 1200r / min for 70min. ④ Stir at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and filter to obtain a slurry ⑤ Apply the slurry obtained above onto 6µm electrolytic copper foil, dry and die-cut to obtain the negative electrode sheet.
[0035] Comparison group 5: The preparation method of the negative electrode sheet of a lithium-ion battery is as follows: Negative electrode active material: graphite / total powder mass = 94.5% Negative electrode conductive agent: conductive carbon black SuperP / total powder mass = 1.5% Negative electrode PAA powder: PAA powder / total powder mass = 4%. The amount of PAA powder added in the first step is 0.5 of the total PAA powder. Negative electrode additive: EC, additive is 2% of the mass of negative electrode active material Anode solvent: deionized water Negative electrode current collector: 6µm electrolytic copper foil.
[0036] The method for preparing the negative electrode slurry of a lithium ion battery comprises the following steps: ① Take 100kg of graphite, 2.11kg of PAA and 1.58kg of conductive carbon black and add them into a stirring tank. Stir at a revolution rate of 10r / min and a rotation rate of 300r / min for 25min. ② Add 45.35kg of deionized water and stir at a revolution rate of 15r / min and a rotation rate of 300r / min for 70min ③ Add 2.11kg PAA, 60.64kg deionized water, and 2kg EC, and stir at a revolution rate of 18r / min and a rotation rate of 1200r / min for 70min. ④ Stir at a revolution rate of 10 r / min and a rotation rate of 300 r / min for 30 min, and filter to obtain a slurry ⑤ Apply the slurry obtained above onto 6µm electrolytic copper foil, dry and die-cut to obtain the negative electrode sheet.
[0037] The following table shows the peeling force and electrode resistivity test results of Examples 1-3 and Comparative Groups 1-5.
[0038] Table 4. Electrode sheet resistivity test of the embodiment and comparison group experiment Negative electrode material / total powder mass Conductive agent / total powder mass Proportion of dispersant and negative electrode binder PAA / total powder mass First step PAA / Total PAA Peel force N / m Electrode sheet resistivity (Ω·cm) Example 1 94.70% 1.50% 3.80% / / 10.8 40.23 Example 2 93.70% 2.50% 3.80% / / 8.8 30.55 Example 3 92.20% 4.00% 3.80% / / 6.9 25.87 Comparison group 1 96.00% 1.50% / 2.50% 0.50 12.2 30.68 Comparison group 2 95.00% 2.50% / 2.50% 0.50 10.6 22.11 Comparison group 3 93.50% 4.00% / 2.50% 0.50 9.3 17.83 Comparison group 4 96.00% 1.50% / 2.50% 0.80 12.1 29.39 Comparison group 5 94.50% 1.50% / 4.00% 0.50 16.5 24.74 It can be concluded from the above table that the negative electrode plate of the lithium ion battery of the present invention has a high negative electrode main material content, a low plate resistivity, and a large plate peeling force, while the negative electrode plates of the lithium ion battery of Examples 1 to 3 reduce the plate resistivity by increasing the conductive agent content, resulting in a low negative electrode main material content, an increased conductive agent content, an unchanged binder content, and a reduced peeling force.
[0039] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode slurry for a lithium ion battery, characterized in that: include: S1, providing a negative electrode active material, a conductive agent and a PAA binder according to 92-97%, 0.5-4% and 2.5-4% of the total mass ratio, and providing an auxiliary agent according to a ratio of 0.8%-3.0% of the mass of the negative electrode active material, wherein the auxiliary agent is one or a combination of ethanol, isopropanol, N-methylpyrrolidone, ethylene carbonate, diethyl carbonate, dimethyl carbonate, and ethylene glycol; S2, mixing the negative electrode active material, the conductive agent and 50%-70% of the PAA binder, adding a solvent, kneading and stirring to obtain a mixture; S3, adding the remaining PAA binder, the remaining solvent and the auxiliary agent to the mixture obtained in step S2, and stirring to obtain the lithium ion battery negative electrode slurry; The solvent used in step S2 accounts for 35-45% of the total solvent, and the total mass of the solvent in step S2 and step S3 accounts for 25-65% of the total mass of the negative electrode slurry.
2. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The solvent is deionized water.
3. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 1, characterized in that: The negative electrode active material comprises one or a combination of graphite, soft carbon, hard carbon, silicon oxygen, silicon carbon, silicon alloy, tin alloy, and other non-carbon negative electrode materials; the conductive agent comprises one or a combination of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, VGCF, and conductive paste.
4. The method for preparing a negative electrode slurry for a lithium ion battery according to claim 3, characterized in that: The negative electrode active material is graphite, and the conductive agent is carbon black.
5. The method for preparing negative electrode slurry for lithium ion batteries according to claim 3, characterized in that: The step S2 specifically includes: slowly stirring and mixing the negative electrode active material, the conductive agent and 50%-70% of the PAA binder at a revolution speed of 10-15 r / min and a rotation speed of 200-400 r / min, and then adding a solvent to knead and stir to obtain the mixture; the step S specifically includes: adding the remaining PAA binder, solvent and auxiliary agent to the mixture obtained in step S2, and rapidly stirring at a revolution speed of 15-18 r / min and a rotation speed of 1200-1800 r / min to obtain the lithium ion battery negative electrode slurry.
6. A negative electrode slurry for a lithium ion battery, characterized in that: The negative electrode slurry for a lithium-ion battery is prepared by the method for preparing the negative electrode slurry for a lithium-ion battery as described in any one of claims 1 to 5.
7. A negative electrode plate for a lithium-ion battery, comprising a current collector and a negative electrode active material layer formed by drying a negative electrode slurry coated on the current collector, characterized in that: The negative electrode slurry is the negative electrode slurry for a lithium ion battery according to claim 6.
8. The negative electrode plate of a lithium-ion battery according to claim 7, characterized in that: The current collector is one of copper foil, microporous copper foil, coated copper foil, aluminum foil, microporous aluminum foil, and coated aluminum foil, and has a thickness of 3 μm-20 μm.
9. The negative electrode plate of a lithium-ion battery according to claim 8, characterized in that: The current collector is 6µm copper foil.
10. A lithium ion battery, characterized in that: It comprises a negative electrode plate of a lithium-ion battery as described in any one of claims 7 to 9.